ANALISIS BEBAN KERJA MENTAL PADA STAFF OFFICER ADARO SERVICE SITE ADMO MENGGUNAKAN METODE NASA-TLX - Darsini, Darsini; Wahyu Purnomo, Andi (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2024)
Human Resources (HR) is a workforce, employees, who work in a company. Human resources in a company are one of the important aspects to increase the effectiveness and efficiency of a company. Staff Officer is one part of the company that has an important role in carrying out production activities. Adaro Service Company in the department plant has a Key Performent Indicator PA target of 92%, this target triggers increased fatigue for staff officers, and creates an effect of excessive mental workload, thus reducing productivity figures. This study aims to analyze the mental workload on staff officers, and find out what factors cause the mental workload of staff officers. The method used in this study is the NASA-TLX method. The results of this study indicate that the level of mental workload indicators for staff officers is in the high category. The highest indicator is the Frustration Level (TF) score of 24%, and factors that cause high mental workload are influenced by human factors and method factors